2020
DOI: 10.1162/jocn_a_01588
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Activity during a Daytime Nap Facilitates Working Memory Improvement

Abstract: Recent investigations have implicated the parasympathetic branch of the autonomic nervous system in higher-order executive functions. These actions are purported to occur through autonomic nervous system's modulation of the pFC, with parasympathetic activity during wake associated with working memory (WM) ability. Compared with wake, sleep is a period with substantially greater parasympathetic tone. Recent work has reported that sleep may also contribute to improvement in WM. Here, we examined the role of card… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…However, not all studies report a consistent association between SOs and WM [13,36,37], and few accounts for autonomic activity. Chen and colleagues reported that vagal activity during SWS was a better predictor of WM improvement than SWA or vagal activity during wake [19]. In the current work, we found that changes in vagal autonomic activity during SWS, but not SOs per se, was critical for WM performance improvement.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…However, not all studies report a consistent association between SOs and WM [13,36,37], and few accounts for autonomic activity. Chen and colleagues reported that vagal activity during SWS was a better predictor of WM improvement than SWA or vagal activity during wake [19]. In the current work, we found that changes in vagal autonomic activity during SWS, but not SOs per se, was critical for WM performance improvement.…”
Section: Discussionsupporting
confidence: 57%
“…Recent studies have shown that WM improvement only occurs when the interval between training sessions contains nocturnal (Zinke et al, 2018;Kuriyama et al, 2008) or daytime sleep (Lau et al, 2015). Given that NREM sleep is a period of vagal dominance compared with wake, a recent study identified vagal HF HRV during NREM as a strong predictor of WM improvement (Chen, Whitehurst, et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…These studies support the notion that naps, like nighttime sleep, may serve as a mini-cardiovascular break. Further, and aligned with the Neurovisceral Integration Model, studies have shown that parasympathetic activity during a daytime nap facilitates improvement in long-term memory (Whitehurst et al, 2016) and working memory (Chen et al, 2020a). Furthermore, these previous investigations did not directly address whether cardiovascular benefits during a nap are sleep-specific or whether benefits can also be achieved from a comparable duration of quiet wake during the day.…”
mentioning
confidence: 99%
“…The interplay between the heart and brain has been identified during sleep at both broad and specific-feature levels. Broadly for example, each sleep stage is characterized by a specific EEG and ANS profile, with greater overall parasympathetic activity (HF-HRV) during NREM compared to waking or REM [5,8,9,11]. Brandenburger et al (2001) also found that as slow waves dissipated with reducing homeostatic sleep pressure across the night, LF/HF HRV rose, suggesting an inverse relationship between the two.…”
Section: Coupling Between the Central And Autonomic Nervous Systems Imentioning
confidence: 99%
“…Cardiac vagal activity, as measured by high frequency heart rate variability (HF HRV: 0.14 -0.4Hz), is a traditional measure of parasympathetic activity [30]. Greater HF HRV during wake is related to better physical health and emotion regulation, and recent evidence links HF HRV during sleep to enhanced memory [1,9,10,52]. In young, healthy people, a balance exists between activity in the sympathetic and parasympathetic branches, moving from a sympathetic-dominant state during wakefulness to parasympathetic dominant state during NREM sleep [5,8,9,20,51].…”
Section: Introductionmentioning
confidence: 99%